Pendataan Kader Muhammadiyah di Kecamatan Bungin Enrekang - Ismaya, Ismaya; Elihami, Elihami; Galib, Andi Ahmad Chabir; Ridwan, Ridwan; Suleman, Samira; Nawis, Andi Nurul Azriana A.; Nurmilasari, Nurmilasari; Lisa, Lisa (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Muhammadiayah is a large organization in Indonesia that operates in the religious realm to become a force to strengthen the unity of the Muslim Ummah. The existence of this organization cannot be separated from the role of the organization's roots which lie in the branches and branches. This activity aims to collect data on DAD Muhammadiyah cadres in order to provide a real picture of the current condition of branches and branches. This activity was carried out in Bungin District, Enrekang Regency. The method for implementing activities uses 2 (two) techniques, namely online and also offline data collection. The activity was carried out for 3 months, namely from September to November 2023. The result of the activity was the existence of a database about Muhammadiyah cadres in Bungin District, Enrekang Regency.